1995
DOI: 10.1111/jon1995519
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐enhanced Magnetic Resonance Imaging of the Lumbosacral Roots in the Dysimmune Inflammatory Polyneuropathies

Abstract: The diagnosis of acute Guillain-Barré syndrome and chronic inflammatory demyelinating polyradiculoneuropathy is based on clinical characteristics, abnormalities on nerve conduction studies, and nerve biopsy specimens indicating demyelination. Inflammation and edema are also common findings in nerve specimens. Immunotherapy is helpful in these dysimmune conditions. Occasionally the diagnosis is difficult to make, particularly when electrophysiological testing or nerve biopsy findings are not characteristic. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 19 publications
0
10
1
Order By: Relevance
“…Several studies have revealed abnormal enhancement of spinal nerve roots [2,3,5,9 -13], which has also been demonstrated in Guillain -Barré syndrome [29,30]. Hypertrophy of nerve roots has often been described in combination with abnormal enhancement [2,3,5,11 -13], showing spinal stenosis in some cases [4,5,12,13].…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have revealed abnormal enhancement of spinal nerve roots [2,3,5,9 -13], which has also been demonstrated in Guillain -Barré syndrome [29,30]. Hypertrophy of nerve roots has often been described in combination with abnormal enhancement [2,3,5,11 -13], showing spinal stenosis in some cases [4,5,12,13].…”
Section: Discussionmentioning
confidence: 94%
“…The first reports on MRI findings in patients affected by CIDP described nerve root enlargement mostly within the cauda equina and spinal roots [13,14], with different degrees of gadolinium enhancement, which is not considered sufficient for a differential diagnosis with GuillanBarrè syndrome (GBS) [15,16].…”
Section: Magnetic Resonance Imaging and Ultrasound In Cidpmentioning
confidence: 99%
“…Such enhancement is a non-specific finding which has previously been documented in Guillain-Barré syndrome, CIDP, meningeal carcinomatosis, infectious polyradiculitis, arachnoiditis, and sarcoidsois 10. Nerve root enhancement has not previously been reported either in systemic lupus erythematosus associated, or in vasculitic, polyradiculopathy.…”
Section: Discussionmentioning
confidence: 74%